2013
DOI: 10.1212/wnl.0b013e31829bfde3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of stroke and its subtypes in Chinese vs white populations

Abstract: Objective: We aimed to systematically assess the evidence for differences in the incidence of stroke and distribution of its subtypes in Chinese compared with white populations. Methods:We comprehensively sought studies conducted since 1990 in Chinese populations of 1) first-ever stroke incidence (community-based studies only), and 2) pathologic types/subtypes of stroke (hospital-or community-based studies of first-ever or recurrent strokes). We identified community-based studies in white populations from a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
304
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(331 citation statements)
references
References 26 publications
20
304
6
1
Order By: Relevance
“…Carriers of the OPG‐1181 (rs2073618) C/C genotype had a significantly increased risk of intracerebral hemorrhage (ICH), but no associations were found between C/C genotype and ischemic stroke, and nor between the OPG‐T950C (rs2073617) and stroke subtypes (Tsai et al. 2013), which is consistent with our observation for this SNP. The current study showed the rs2073618 G/G variant genotype was associated with hemorrhagic stroke in Chinese population after 50 years, but not with the younger population of ≤50 years old.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Carriers of the OPG‐1181 (rs2073618) C/C genotype had a significantly increased risk of intracerebral hemorrhage (ICH), but no associations were found between C/C genotype and ischemic stroke, and nor between the OPG‐T950C (rs2073617) and stroke subtypes (Tsai et al. 2013), which is consistent with our observation for this SNP. The current study showed the rs2073618 G/G variant genotype was associated with hemorrhagic stroke in Chinese population after 50 years, but not with the younger population of ≤50 years old.…”
Section: Discussionsupporting
confidence: 93%
“…OPG‐G1181C (rs2073618) is the only polymorphism in a coding region of TNFRSF11B , while OPG‐T950C (rs2073617) is located in its promoter region (Tsai et al. 2013). This G/C variation results in lysine/asparagine change in the single peptide of OPG, which may have an effect on intracellular trafficking or export efficiency of the final protein and local concentration of OPG in the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute excess would be expected to be bigger in individuals with pre-existing cerebrovascular disease 38 and in populations (such as Asia) where the underlying rates of haemorrhagic stroke are higher. 235 However, statin therapy has been found to reduce the overall risk of stroke in many different settings (including in people who have already had a stroke 38 or have hypertension 103 ) irrespective of the underlying risk of vascular disease. 32 For example, the increase in haemorrhagic stroke is outweighed by the reduction in the risk of ischaemic stroke, as well as in other occlusive vascular events and deaths, even among individuals with a 5-year risk of major vascular events below 10%.…”
Section: Probable Increases In Rates Of Haemorrhagic Strokementioning
confidence: 99%
“…66 Extensive epidemiological data demonstrate marked ethnic differences in stroke incidence and the distribution of subtypes. For example, intracranial stenosis and intracerebral haemorrhage are more frequent in Far East Asian populations compared with white populations, 67,68 and small-vessel disease is more common among individuals of African ancestry living in London, UK or in the USA than in white individuals living in the same countries. 47,69 However, few studies have been conducted in non-white populations, and more are needed.…”
Section: Sex and Ethnic Differencesmentioning
confidence: 99%